Integrated treatment for co-occurring disorders : treating people, not behaviors - Klott, Jack (John Wiley & Sons, Inc., 2013)
The definitive guide to identify, assess, and create individualized treatment plans for high-risk clients who suffer from challenging co-occurring disorders ""Treat the person and not the diagnosis. Respect that all behaviors are purposeful. Remain mindful that nobody changes behaviors without motivation. These essential guiding principles are the framework of this book. They will be repeated quite often as we examine the challenging population of men and women with co-occurring disorders.""--Integrated Treatment for Co-Occurring Disorders Annual studies reveal that 70.